Ministry Of Trade and Industry Decree No. 43 Of The Year 2016 Regarding The Amendment Of The Rules Organizing The Registration Of Factories Qualified To Export Products Thereof To The Arab Republic Of Egypt = وزارة التجارة والصناعة قرار رقم 43 لسنة 2016 بشأن تعديل القواعد المنظمة لتسجيل المصانع المؤهلة لتصدير منتجاتها إلى جمهورية مصر العربية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic